2019
DOI: 10.1210/jc.2018-02557
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uromodulin Is Associated With But Does Not Predict Type 2 Diabetes in Elderly KORA F4/FF4 Study Participants

Abstract: Aims Serum uromodulin has recently emerged as promising biomarker for kidney function and was suggested to be associated with type 2 diabetes (T2D) in patients with coronary heart disease. Here, we analyzed the association of serum uromodulin with T2D in the population-based KORA F4/FF4 study. Methods In 1119 participants of the KORA F4 study aged 62 to 81 years, serum uromodulin was measured, and the association of serum uro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Continuous variables were transformed to a Gaussian distribution by the probability integral transformation followed by an inverse transform sampling and were used as in calculations per one standard deviation. In logistic and linear regression analyses, the association of sUmod with the respective dependent variables was adjusted for covariates in 5 models ( model 1 : sex, age (which are both related to hypertension and have been shown to be associated with sUmod [ 18 ]); model 2 : model 1 plus eGFR (which was decreased in hypertensive participants and is strongly related to sUmod [ 12 ]); model 3 : model 2 plus BMI (which is associated with sUmod [ 20 ]), fasting glucose (associated with sUmod [ 18 ]), current smoking, previous stroke and myocardial infarction; model 4 : model 3 plus arterial hypertension; model 5 : model 4 plus use of beta-blockers, angiotensin-converting enzyme inhibitors and angiotensin receptor antagonists, since these medications might influence the renin-aldosterone-angiotensin system). Model 1 and 2 were applied for all analyses, model 3 for the assessment of arterial hypertension, model 4 for CT-proET-1 and model 5 for renin and aldosterone as dependent variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous variables were transformed to a Gaussian distribution by the probability integral transformation followed by an inverse transform sampling and were used as in calculations per one standard deviation. In logistic and linear regression analyses, the association of sUmod with the respective dependent variables was adjusted for covariates in 5 models ( model 1 : sex, age (which are both related to hypertension and have been shown to be associated with sUmod [ 18 ]); model 2 : model 1 plus eGFR (which was decreased in hypertensive participants and is strongly related to sUmod [ 12 ]); model 3 : model 2 plus BMI (which is associated with sUmod [ 20 ]), fasting glucose (associated with sUmod [ 18 ]), current smoking, previous stroke and myocardial infarction; model 4 : model 3 plus arterial hypertension; model 5 : model 4 plus use of beta-blockers, angiotensin-converting enzyme inhibitors and angiotensin receptor antagonists, since these medications might influence the renin-aldosterone-angiotensin system). Model 1 and 2 were applied for all analyses, model 3 for the assessment of arterial hypertension, model 4 for CT-proET-1 and model 5 for renin and aldosterone as dependent variables.…”
Section: Methodsmentioning
confidence: 99%
“…The physiological role of uromodulin in the systemic circulation is still unknown. However, sUmod seems to play an important role beyond renal homeostasis, since it is inversely associated with all-cause and cardiovascular mortality [ 14 17 ] and with various cardiovascular risk factors, such as diabetes [ 18 , 19 ], the metabolic syndrome and its single components including elevated blood pressure [ 20 ]. In contrast, genome-wide association studies [ 21 24 ] and animal models [ 25 , 26 ] show an increased risk of arterial hypertension in uromodulin-increasing UMOD loci variants, and uromodulin has even been suggested to be a possible target for blood pressure control [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the validation of a complementary kidney tissue marker not directly depending on eGFR is especially crucial for older people. Recently it has been shown that independent of eGFR, sUmod is inversely associated with type 2 diabetes, obesity and metabolic syndrome and its single components, including elevated blood pressure [ 34–36 ], providing the rationale to assume that sUmod might be a promising candidate biomarker for kidney function in an elderly general population typically having a high frequency of these risk factors. We here investigated the association of sUmod with kidney function cross-sectionally and longitudinally in elderly participants of the population-based Cooperative Health Research in the Region of Augsburg (KORA) F4/FF4 cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Scheurlen et al described an increase of sUmod following Roux-en-Y-gastric bypass in patients with severe obesity, indicating improved ‘kidney health’ or renal reserve after bariatric surgery, which was not detectable by traditional kidney function markers (26). We (25) and others (27) previously showed that sUmod was inversely associated with type 2 diabetes independently of the eGFR. Thus, sUmod possibly represents a tissue-specific marker for early diabetic nephropathy that escapes GFR estimates due to diabetes-related glomerular hyperfiltration.…”
Section: Discussionmentioning
confidence: 67%
“…This may serve as one explanation of an inverse connection of uromodulin and metabolic disturbances. In our cohort, sUmod was inversely associated with hsCRP (25). However, adjustment for hsCRP only moderately attenuated the association of sUmod with the metabolic syndrome and its components, indicating that chronic subclinical inflammation as assessed by hsCRP is not the only factor explaining the interplay of the metabolic syndrome and sUmod.…”
Section: Discussionmentioning
confidence: 76%